Odorant binding proteins: a biotechnological tool for odour control - Silva, Carla (2014)
The application of an odorant binding protein for odour control and fragrance delayed release from a textile surface was first explored in this work. Pig OBP-1 gene was cloned and expressed in Escherichia coli, and the purified protein was biochemically characterized. The IC50 values (concentrations of competitor that caused a decay of fluorescence to half-maximal intensity) were determined for four distinct fragrances, namely, citronellol, benzyl benzoate, citronellyl valerate and ethyl valerate. The results showed a strong binding of citronellyl valerate, citronellol and benzyl benzoate to the recombinant protein, while ethyl valerate displayed weaker binding. Cationized cotton substrates were coated with porcine odorant binding protein and tested for their capacity to retain citronellol and to mask the smell of cigarette smoke. The immobilized protein delayed the release of citronellol when compared to the untreated cotton. According to a blind evaluation of 30 assessors, the smell of cigarette smoke, trapped onto the fabrics' surface, was successfully attenuated by porcine odorant binding protein (more than 60 % identified the weakest smell intensity after protein exposure compared to β-cyclodextrin-treated and untreated cotton fabrics). This work demonstrated that porcine odorant binding protein can be an efficient solution to prevent and/or remove unpleasant odours trapped on the large surface of textiles. Its intrinsic properties make odorant binding proteins excellent candidates for controlled release systems which constitute a new application for this class of proteins.